2021
DOI: 10.1002/jor.25104
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain: What is the role of YouTube content in patient education?

Abstract: The aim of this study was to characterize the educational quality and reliability of YouTube videos related to low back pain (LBP) as well as to identify factors associated with the overall video quality. A review of YouTube was performed using two separate search strings. Video‐specific characteristics were analyzed for the first 50 videos of each string. Seventy‐seven eligible videos were identified as a result. The mean Journal of the American Medical Association score was 2.25 ± 1.09 (range: 0–4) out of 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
1
12
1
1
Order By: Relevance
“…The exercise intervention is considered an integral part of CLBP management and has been reported to reduce pain and improve function in patients with CLBP; however, there are challenges in exploring effective exercise types and continuing exercise [ 43 , 44 ]. In recent years, various digital interventions have attempted to address these challenges [ 45 - 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exercise intervention is considered an integral part of CLBP management and has been reported to reduce pain and improve function in patients with CLBP; however, there are challenges in exploring effective exercise types and continuing exercise [ 43 , 44 ]. In recent years, various digital interventions have attempted to address these challenges [ 45 - 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that attempting to learn specific procedures, such as cardiopulmonary resuscitation, through self-learning videos is a viable approach ( 21 ). Therefore, it is important to ensure the accuracy of the content in these videos ( 22 , 23 ). When we analyzed the relationship between video quality and the number of video views, we also found that lower-quality videos had significantly more views than higher-quality videos ( p = 0.043) and that the differences among the numbers of views, comments, and replies were too large.…”
Section: Discussionmentioning
confidence: 99%
“…Cassidy et al ( 46 ) determined that the mean JAMA score and anterior cruciate ligament-specific score (maximum of 25 points) were 2.4 and 5.5, respectively. Hornung et al ( 47 ) determined that the mean JAMA, GQS, and low back pain-specific score (maximum of 15 points) were 2.25, 2.29, and 3.83, respectively. Together, these data suggested that the reliability and quality of the YouTube videos on orthopedic disorders were low.…”
Section: Discussionmentioning
confidence: 99%